1975
DOI: 10.1093/jnci/55.6.1461
|View full text |Cite
|
Sign up to set email alerts
|

Brief Communication: Growth of Human Normal and Neoplastic Mammary Tissues in the Cleared Mammary Fat Pad of the Nude Mouse2

Abstract: Dysplastic and malignant human breast tissues were grown successfully in the cleared mammary fat pads (CFP) of nude mice. The mammary fat pads were cleared while the mice were in a germfree isolator. Prepared mice were removed fron the germfree enviornment to facilitate transplantation of the human mammary tissue into their CFP and subsequently were maintained in sterile laminar flow racks.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
37
1

Year Published

1977
1977
2007
2007

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(39 citation statements)
references
References 0 publications
1
37
1
Order By: Relevance
“…Unlike their murine counterparts, the introduced human MECs fail to colonize these fat pads and thus do not develop into ductal and lobular structures (2,3). To circumvent this issue, researchers have attempted to recreate functional tissues by transplanting normal breast tissue fragments or collagen-embedded dissociated human MECs either s.c. or beneath the renal capsule of immunocompromised nude mice (2)(3)(4)(5)(6)(7)(8)(9)(10). Although the tissue fragments and dissociated cells survive and respond to hormone stimulation, no outgrowth or expansion of the transplanted tissues has been observed.…”
mentioning
confidence: 99%
“…Unlike their murine counterparts, the introduced human MECs fail to colonize these fat pads and thus do not develop into ductal and lobular structures (2,3). To circumvent this issue, researchers have attempted to recreate functional tissues by transplanting normal breast tissue fragments or collagen-embedded dissociated human MECs either s.c. or beneath the renal capsule of immunocompromised nude mice (2)(3)(4)(5)(6)(7)(8)(9)(10). Although the tissue fragments and dissociated cells survive and respond to hormone stimulation, no outgrowth or expansion of the transplanted tissues has been observed.…”
mentioning
confidence: 99%
“…Metastasis can be also studied by transplantation of human tumor cells in mice, a technique that is restricted to immune-compromised or immune deficient animals because of the inevitable host versus graft reactions [53,54]. As a consequence, the contribution of an intact immune system-which plays a key role in the metastatic processcannot be studied in these xenograft models.…”
Section: Xenograft Modelsmentioning
confidence: 99%
“…Study of stromal-epithelial interactions in the human mammary gland has proven difficult, but with increasing understanding, better in vivo models have evolved. Outzen & Custer (1975) transplanted pieces of normal human breast into cleared fat pads of athymic nude mice and reported that the tissue produced outgrowths that proliferated into the mouse mammary fat pads. In contrast, when Jensen & Wellings (1976) repeated this experiment, they did not observe growth of transplanted normal human breast tissue into the mouse mammary fat pad.…”
Section: Human Mammary Cells In Culture: In Vitro Studies Of Human Epmentioning
confidence: 99%